2016
DOI: 10.1038/nmat4692
|View full text |Cite
|
Sign up to set email alerts
|

Reversible phase modulation and hydrogen storage in multivalent VO2 epitaxial thin films

Abstract: Hydrogen, the smallest and the lightest atomic element, is reversibly incorporated into interstitial sites in vanadium dioxide (VO2), a correlated oxide with a 3d(1) electronic configuration, and induces electronic phase modulation. It is widely reported that low hydrogen concentrations stabilize the metallic phase, but the understanding of hydrogen in the high doping regime is limited. Here, we demonstrate that as many as two hydrogen atoms can be incorporated into each VO2 unit cell, and that hydrogen is rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
381
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(413 citation statements)
references
References 43 publications
30
381
0
2
Order By: Relevance
“…Explained in the context of crystal-field theory [16,17], the H-doping induced band structure evolutions is represented in Fig. 1 [12,15]. From the in-situ R-T measurement in vacuum conditions, the insulating H-VO 2 (I) gradually became a metallic sample as shown in Fig.1 (c).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Explained in the context of crystal-field theory [16,17], the H-doping induced band structure evolutions is represented in Fig. 1 [12,15]. From the in-situ R-T measurement in vacuum conditions, the insulating H-VO 2 (I) gradually became a metallic sample as shown in Fig.1 (c).…”
mentioning
confidence: 99%
“…It is reported that hydrogen incorporated into M-VO 2 crystals can stabilize the metallic VO 2 phase at room temperature [10][11][12][13][14] and further lead to an insulating phase in the high doping regime [15]. Explained in the context of crystal-field theory [16,17], the H-doping induced band structure evolutions is represented in Fig.…”
mentioning
confidence: 99%
“…The rutile phase is however predicted by DFT to be the most stable phase; more importantly, it is stabilized by Li insertion which makes it more stable than the semiconductor phase [34]. Stabilization of rutile VO 2 was also reported in experimental studies on hydrogen and boron doping in VO 2 nanowires [133,134]. Moreover, the X-ray diffraction (XRD) measurements identified the presence of VO 2 (R) phase during Li-ion battery cycling, consistent with our calculations [124].…”
Section: Interactions Of LI Na Na Mg and Al With Different Phasesmentioning
confidence: 86%
“…The switching effect is a sharp, significant, and reversible change in the system conductivity under the action of the applied electric field. Doping VO 2 with various metals and hydrogen allows one to control the value of [1,[7][8][9][10] and, accordingly, the S-shaped I-V characteristic parameters, for example, the threshold voltage th . On the other hand, the study of the MIT in vanadium dioxide, doped with hydrogen or metals with a 2 Advances in Condensed Matter Physics valence greater than 4 (e.g., W 6+ ), is of great importance from the viewpoint of further understanding the transition mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…This fact would seem to make it possible to consider the MIT in this material as a structural Peierls transition [1] with the charge density wave formation. Meanwhile, there exists a large amount of experimental data that support the Mott electron-correlation transition scenario [2,6,[8][9][10] as the MIT initiating mechanism in vanadium dioxide. In this context, doping, which leads to an increase in the free carrier concentration, is an effective way to either confirm or refute the hypothesis of the Mott transition in vanadium dioxide [8][9][10].…”
Section: Introductionmentioning
confidence: 99%